Riedel’s Lobe: Clinical Importance of a Rare Variant in Liver Morphology - Juferdy Kurniawan; Dewi Anggraeni; Esthika Dewiasty; Lutfie Lutfie (Acta Medica Indonesiana, 2017)
Riedel’s lobe is a normal variant form of right liver lobe rarely found. Here we report a case of 38 years old female with an incidental finding not revealed in physical examination, but then known to have hepatomegaly by gynecological ultrasonography. Diagnosis of Riedel’s lobe was strengthened by similar results on hepatobiliary ultrasonography, abdominal MRI, and diagnostic laparoscopy. Our patient was discharged and had follow up examination three months later. Knowledge regarding this anomaly is essential to be understood because the finding of accessory liver lobe does not always remain asymptomatic as in our patient, but rather can be related to significant clinical complication.